2013
DOI: 10.1002/2013jd019619
|View full text |Cite
|
Sign up to set email alerts
|

The angular distribution of energetic electron and X‐ray emissions from triggered lightning leaders

Abstract: [1] We investigate individual X-ray bursts from lightning leaders to determine if energetic electrons at the source (and hence X-rays) are emitted isotropically or with some degree of anisotropy. This study was motivated by the work of Saleh et al. (2009), which found the falloff of X-rays in concentric radial annuli, covering all azimuthal directions in each annulus, from the lightning channel to be most consistent with an isotropic electron source. Here we perform a statistical analysis of angular and spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…However, Saleh et al (2009) found, for triggered-lightning leaders, that the source electrons are probably emitted isotropically. According to a more recent study (Schaal et al, 2013), the emission may be not isotropic for individual leader steps, but is isotropic for all steps combined. Another explanation of the lack of x-rays from some steps, offered by Mallick et al (2012), is that the electric field enhancements (>30 MV/m or so for the case of normal air density), needed for the cold runaway breakdown, are very brief and highly localized, so that in many cases an electron capable of starting the efficient…”
Section: Comparison With Previous Observations and Discussionmentioning
confidence: 99%
“…However, Saleh et al (2009) found, for triggered-lightning leaders, that the source electrons are probably emitted isotropically. According to a more recent study (Schaal et al, 2013), the emission may be not isotropic for individual leader steps, but is isotropic for all steps combined. Another explanation of the lack of x-rays from some steps, offered by Mallick et al (2012), is that the electric field enhancements (>30 MV/m or so for the case of normal air density), needed for the cold runaway breakdown, are very brief and highly localized, so that in many cases an electron capable of starting the efficient…”
Section: Comparison With Previous Observations and Discussionmentioning
confidence: 99%
“…Much of the published research conducted at the International Center for Lightning Research and Testing (ICLRT) during the past seven years has focused on the physics and mechanisms of low-altitude, negative polarity lightning leader propagation and the associated electromagnetic emissions from electrostatic to gamma radiation [e.g., Biagi et al, 2009Biagi et al, , 2010Biagi et al, , 2014Dwyer et al, 2003Dwyer et al, , 2004Dwyer et al, , 2005Dwyer et al, , 2011Gamerota et al, 2014aGamerota et al, , 2014bGamerota et al, , 2015Hill et al, 2011Hill et al, , 2012Howard et al, 2008Howard et al, , 2010Howard et al, , 2011Saleh et al, 2009;Schaal et al, 2013Schaal et al, , 2014. The ICLRT is a facility jointly operated by the University of Florida and the Florida Institute of Technology and is located about 45 km northeast of Gainesville, FL.…”
Section: Introductionmentioning
confidence: 99%
“…The ICLRT is one of only two sites in the United States and four in the world where lightning is presently artificially initiated ("triggered") using the rocket-and-wire technique. Coordinated high-speed video, radio-frequency electromagnetic field, and energetic radiation (X-rays and gamma rays) measurements of triggered and natural lightning leaders propagating at low altitude have allowed ICLRT researchers to gain better understanding of the leader step formation process [e.g., Biagi et al, 2009Biagi et al, , 2010Biagi et al, , 2014Gamerota et al, 2014aGamerota et al, , 2014bGamerota et al, , 2015Hill et al, 2011;Howard et al, 2010Howard et al, , 2011 and the related high-energy emissions [e.g., Dwyer et al, 2003Dwyer et al, , 2004Dwyer et al, , 2005Dwyer et al, , 2011Hill et al, 2012;Howard et al, 2008Howard et al, , 2010Saleh et al, 2009;Schaal et al, 2013Schaal et al, , 2014. Most of these studies have concentrated on the time period extending from several microseconds to several hundred microseconds prior to the return stroke when the propagating leaders are within about 500 m of ground.…”
Section: Introductionmentioning
confidence: 99%
“…Lightning is known to generate microsecond‐fast bursts of X‐ray radiation (Dwyer et al, ; , Dwyer, Rassoul, Al‐Dayeh, et al, ; Dwyer et al, ; Hill, ; Hill et al, ; Howard et al, , ; Mallick et al, ; Montanyà et al, ; Moore et al, ; Saleh et al, ; Schaal et al, , , ; Yoshida et al, ) and electron flux enhancements (Yoshida et al, ). Such bursts were detected from both natural and triggered lightning.…”
Section: Introductionmentioning
confidence: 99%